A simple tool with which to study the course of chronic hand eczema in clinical practice: a reduced‐item score. (22nd July 2013) - van der Valk, Pieter G. M.; van Gils, Robin F.; Boot, Cécile R. L.; Evers, Andrea W. M.; Donders, Rogier; Alkemade, Hans A. C.; Coenraads, Pieter Jan; Rustemeyer, Thomas; van Mechelen, Willem; Anema, Johannes R.
Summary: Background: Physicians need a simple, disease‐specific tool with which to assess disease severity and the effect of therapeutic intervention in patients with chronic hand eczema. The currently available clinical scoring systems include numerous items, which makes them laborious to complete and limit their use in daily practice. Objective: To develop a simple tool with which to assess disease severity of patients with chronic hand eczema. Methods: We evaluated two tools, the Hand Eczema Severity Index (HECSI) and the Hand Eczema Area and Severity score, to determine their ability to predict the Investigator's Global Assessment (IGA) of disease severity in patients with moderate to severe hand eczema. We used a stepwise reduction analysis to determine a minimal set of significantly contributing items for predicting IGA. Results: A three‐item score, based on the highest observed value of induration, fissuring, and scaling, predicted IGA with a correlation of 0.667. The HECSI predicted the IGA with a correlation of 0.675. Conclusion: On the basis of this analysis, we propose a simple tool for clinical decision‐making and evaluation of therapeutic intervention in daily practice.